(untitled) (Revista Contexto & Saúde, 2025)
The research aimed to understand the epidemiological information of the first year of the COVID-19 pandemic in traditional communities in the Amazon. Furthermore, it analyzed the perception of the events and reported the leading practices adopted to mitigate the pandemic. The fieldwork was conducted in two communities: one riverside and one quilombola, both in the municipality of Abaetetuba, in the state of Pará. Representatives and local players from the communities participated in the data collection, after which the information was analyzed qualitatively and quantitatively. The novel coronavirus pandemic has damaged traditional communities, such as unemployment, increased social inequalities, declining public health, more expensive food, and psychological problems. Some actions have been taken by local organizations and NGOs to mitigate the impacts. However, it still has not been enough to guarantee people’s safety from the virus. Although there were no deaths, the number of people infected was undoubtedly higher than expected; in addition, as these are regions far from urban areas, health and social services have become more precarious and almost non-existent.